Pengaruh Wisata Kuliner Berbasis Produk Aci Terhadap Keputusan Berkunjung Wisatawan Ke Kota Garut - Surya Aditya Wahyono; Ita Karnita; Ghini Kuntala Devi; Sara Rabasari (Journal of Innovation Research and Knowledge, 2026)
The city of Garut is part of West Java province. Garut Regency is known for its diverse tourism potential, including natural, cultural, and culinary attractions. One of the unique aspects of Garut’s cuisine is the use of aci (tapioca flour) as a staple ingredient in various local dishes. These aci-based dishes have a distinctive flavor, are relatively affordable, and are easily found throughout the city, making them a potential draw for tourists. Garut is often considered a “paradise for aci-based foods” due to a combination of cultural factors, readily available ingredients, and the culinary creativity of its people. Garut and the surrounding areas in West Java are regions with abundant cassava production. Tapioca flour (aci) is processed from this cassava. Because it is readily available and inexpensive, aci has become a very popular staple ingredient. The potential of local aci-based foods can serve as a solution for developing innovative and affordable menu items. These local food ingredients can be leveraged as a key attraction to draw tourists to the city of Garut. The research method used in this study is a descriptive research method, while the data analysis technique employed is quantitative data analysis. The research location is the Garut culinary tourism area. The target outcome of this study is publication in a nationally accredited Sinta 3 journal. The resulting TKT will be at Level 2.